If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-24) + -17 = x -24 + -17 = x Combine like terms: -24 + -17 = -41 -41 = x Solving -41 = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -41 + -1x = x + -1x Combine like terms: x + -1x = 0 -41 + -1x = 0 Add '41' to each side of the equation. -41 + 41 + -1x = 0 + 41 Combine like terms: -41 + 41 = 0 0 + -1x = 0 + 41 -1x = 0 + 41 Combine like terms: 0 + 41 = 41 -1x = 41 Divide each side by '-1'. x = -41 Simplifying x = -41
| 2a+12=8a-3 | | b+4/3=9 | | 10x-4(2x+7)=-12 | | b+3/-4=-16 | | 7(j-5)=-14 | | c/4=6+12 | | b+4/-5=-5 | | 6=v/9.6 | | 5x+7y=1000 | | 3bsquared=3 | | -55=.625r | | 4a-2a+11=5+5a | | 16=r/8 | | 15=-8+z/5 | | a+22=5 | | (6u^5+10(u^2)v^5)/8(u^5)y | | 6r^2-19r+15=0 | | 18w+50=284 | | 6x+8y=2200 | | -10x^2=-540 | | -25x=-6x+3+92 | | 6-5x+x=-10 | | a/5=35 | | 7x+6-5x=14 | | 4+5x-6x=-4 | | 4d=68 | | 5+y-4y^2-7= | | -99=-p | | 76=4r | | 9=6x-5x-3 | | 3w=-93 | | (6x^2-54)/(9x+27) |